(untitled) (Филолошке студије, 2019)
Demographic, ethnic, religious and cultural composition of the Balkans represents a combine effect of various factors, constituting it into relatively coherent unity. In order to underline the specific qualities and uniqueness of this cultural effect, the author suggests the term Geomythology, claiming its key role in the processes of shaping the cultural topography of the Europe. The paper distinghuishes between three main models of cultural consiousness derived from the three types of cultural geomithology crystalised in the Balkans, 1. The model of Peninsula; 2. The model of the Continent; 3. The model of Hidden Valley, all three executing their mutual impact through the cross examination of self consiousness (self reception), politics, and that of esthetics, promoting them into three main factors of its identity.